Influence of Obstacles on the Use of the Danger Zone on Railway Platforms - Thurau, Jasmin; Keusen, Nicolas (Collective Dynamics, 2020)
Growing passenger numbers and the lack of space available led to research on pedestrians’ behaviour on railway platforms in Switzerland. By using stereo sensors, pedestrians’ tracks were collected on a platform in the train station of Bern. The analysis of pedestrians stepping into the danger zone showed clearly that obstacles have a large influence on the frequencies of pedestrians using the danger zone. By presenting four hypotheses the effect of obstacles on pedestrians’ use of the danger zone on train station platforms is investigated.